Chart your way to profits : the online trader's guide to technical analysis with ProphetCharts - Knight, Tim, 1966- (Wiley, 2010)
A cutting-edge guide to turning technical analysis into trading success, . Chart Your Way to Profits, Second Edition shows you how to use the powerful technology available online in conjunction with technical analysis to assess markets and make the most profitable trading decisions possible. In the book, author Tim Knight discusses the key aspects of technical analysis and reveals how to design your own charts and indicators in a way that enables you to easily monitor the markets and make solid trading decisions. This new edition discusses a wider range of technical tools within ProphetCharts a.